Political Allusions in Book 22 of the Odyssey. Odysseus, Pisistratus and the Deployment of Myth for the Justification of Tyranny - Siropoulos, Spyridon D. (Études helléniques / Hellenic Studies, 2002)
This article considers how political information can be gleaned from literary sources, notably epic and tragedy. Although not history, although manipulated as propaganda at times, the text that the author describes exemplifies how a philosophy of politics relative to democracy in sixth-century Athens may be discerned.